Aksesibilitas Pelabuhan Kuala Tanjung dalam Mendukung Kelancaran Arus Barang di Kawasan Ekonomi Khusus (KEK) Sei Mangkei, Provinsi Sumatera Utara - Suryana, Hendy (Universitas Suryakancana, 2020)
Abstract— The Sei Mangkei Special Economic Zone (SEZ ), which is located in Bosar Maligas District, Simalungun Regency, North Sumatra Province, with an area of 2,002.77 hectares is stipulated by Government Regulation No. 29 of 2012 in the context of developing new industrial areas directed at industries, based on natural and mineral resources and utilizing strategic geographic location. The success and continuity of the Sei Mangkei SEZ will be determined by the transportation and logistics infrastructure that plays a role in the smooth flow of goods transportation from the Sei Mangkei SEZ to the Port of Tanjung which has a strategic role as a marine transportation logistics hub. The purpose and objective of this study is to analyze the prospects and integration of transportation and logistics facilities and infrastructure at the Kuala Tanjung Port-Sei Mangkei SEZ, in order to realize an integrated transportation and logistics facilities and infrastructure for the development of accessibility of the Kuala Tanjung Port-Sei Mangkei SEZ. Based on the research it is known that port accessibility is increasing, rail and truck modes of transportation can be applied and the need for traffic management and engineering. Keywords— SEZ Sei Mangkei; accessibility; Kuala Tanjung Port; supply chain system; train; truck. Abstrak— Kawasan Ekonomi Khusus (KEK) Sei Mangkei yang berlokasi di Kecamatan Bosar Maligas, Kabupaten Simalungun, Propinsi Sumatera Utara, dengan luas 2.002,77 hektar ditetapkan melalui Peraturan Pemerintah Nomor 29 tahun 2012 dalam rangka pengembangan kawasan-kawasan industri baru yang diarahkan pada industri-industri berbasis sumber daya alam dan mineral serta memanfaatkan lokasi geografis yang strategis. Keberhasilan dan kelangsungan KEK Sei Mangkei akan ditentukan oleh infrastruktur transportasi dan logistik yang berperan dalam kelancaran arus angkutan barang dari KEK Sei Mangkei ke Pelabuhan Tanjung yang mempunyai peran strategis sebagai logistics hub transportasi laut. Maksud dan tujuan penelitian ini adalah melakukan analisis tentang prospek dan keterpaduan sarana dan prasarana transportasi dan logistik di Pelabuhan Kuala Tanjung-KEK Sei Mangkei, guna mewujudkan keterpaduan sarana dan prasarana transportasi dan logistik untuk pengembangan aksesibilitas Pelabuhan Kuala Tanjung-KEK Sei Mangkei. Berdasarkan penelitian diketahu bahwa aksesibilitas pelabuhan meningkat, moda angkutan kereta api dan truk dapat diterapkan serta perlunya manajemen dan rekayasa lalu lintas.Kata kunci— KEK Sei Mangkei; aksesibilitas; Pelabuhan Kuala Tanjung; sistem rantai pasok; kereta api; truk.